Research and development of thick rubber bearing for SFR (Hysteresis model for thick rubber bearing based on static loading tests) - Tsuyoshi FUKASAWA; Shigeki OKAMURA; Tomohiko YAMAMOTO; Nobuchika KAWASAKI; Takahiro SOMAKI; Yu SAKURAI; Nobuo MASAKI (Nihon Kikai Gakkai ronbunshu, 2018)
This paper describes the results of the static loading tests using half-scale thick rubber bearings to investigate the fundamental characteristics such as horizontal and vertical restoring force applied for a Sodium-cooled-Fast-Reactor (SFR). The thick rubber bearings, which have a rubber layer roughly two times thicker than conventional rubber bearings, have developed by the authors to ensure seismic safety margins for the components installed reactor building, and to reduce the seismic response not only horizontal direction but also vertical direction. The applicability of design formula to take into account an inner hole for the thick rubber bearing is demonstrated by compared with the results of static loading test, and indicates the non-linear restoring force under beyond-design-basis ground motions. In addition, a new type of hysteresis models that can predict the non-linear characteristics in horizontal and axial direction are proposed, and presents the seismic response results, including beyond-design-basis ground motions, obtained by response analysis using the proposed hysteresis models.